Role of Social Media and Behavioral Finance on Gen Z Travel Behaviour - Ahmad, Siti Yuliandi; Ismail, Shafinar; Saad, Mazni; Hama, Susan (AMER by e-International Publishing House, Ltd., UK, 2025)
Travel decisions among Gen Z are largely shaped by social media engagement, financial literacy, and economic stability, yet the extent to which these factors contribute to travel behaviour remains underexplored. While social media provides real-time travelrecommendations and personalized experiences, it also promotes aspirational lifestyles that may lead to impulsive spending. This study aims to identify the key predictors of Gen Z travel behaviour by examining the role of social media use, social media influence, financial literacy, and financial security. The findings provide important insights for tourism stakeholders, policymakers, and educators in designing travel-related initiatives targeted at Gen Z